2006
DOI: 10.1002/app.23519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of activation temperature on the properties and structure of PAN‐based activated carbon hollow fiber

Abstract: Polyacrylonitrile (PAN) hollow fibers were pretreated with ammonium dibasic phosphate, then further oxidized in air, carbonized in nitrogen, and activated with carbon dioxide. The effects of activation temperature of a precursor fiber on the microstructure, specific surface, poresize distribution, and adsorption properties of PAN-based activated carbon hollow fibers (PAN-ACHF) were studied in this work. After the activation process, the BET surface area of the PAN-ACHF and surface area of mesopores in the PAN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…As a high-melting, rigid and spinnable duroplast, PAN is a very useful raw material for the preparation of microporous activated carbon and carbon fibers by controlled pyrolysis followed by an appropriate chemical and/or thermal activation [1][2][3][4]. PAN-derived activated carbons are applied as the adsorbents for the removal of heavy metal ions and organic pollutants from aqueous solutions as well as volatile organic compounds (VOCs) from exhaust gases [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As a high-melting, rigid and spinnable duroplast, PAN is a very useful raw material for the preparation of microporous activated carbon and carbon fibers by controlled pyrolysis followed by an appropriate chemical and/or thermal activation [1][2][3][4]. PAN-derived activated carbons are applied as the adsorbents for the removal of heavy metal ions and organic pollutants from aqueous solutions as well as volatile organic compounds (VOCs) from exhaust gases [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the PAN‐based activated carbon hollow fibers (PAN‐ACHF) brought on many investigators' interests,3–8 as PAN‐ACHF shows the largest adsorption capacity among the carbon surfaces. In a previous study,9–14 we reported effects of oxidation, carbonization, activation on the properties, and structure of PAN‐ACHF.…”
Section: Introductionmentioning
confidence: 97%
“…15 There are several precursors for the production of carbon fiber, such as polyacrylonitrile (PAN), pitch and cellulose. [16][17][18][19][20] PAN is the most widely used precursor for manufacturing high-performance fibers due to its combination of tensile and compressive properties as well as its high carbon yield. 21 Electrospinning is no longer applied only to organic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The electrospinning technique, invented in the 1930s, has recently gained renewed interest because it can spin a variety of ultrafine polymer fibers at the nanoscale at low cost . There are several precursors for the production of carbon fiber, such as polyacrylonitrile (PAN), pitch and cellulose. PAN is the most widely used precursor for manufacturing high-performance fibers due to its combination of tensile and compressive properties as well as its high carbon yield …”
Section: Introductionmentioning
confidence: 99%